2017
DOI: 10.1016/j.snb.2017.03.106
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably accelerated room-temperature hydrogen sensing of MoO3 nanoribbon/graphene composites by suppressing the nanojunction effects

Abstract: We present a novel hybrid electrodes based on reduced graphene oxide/nickel/zinc oxide heterostructures. The sensor was fabricated by template-free hydrothermal growth of ZnO nanorod arrays on conductive glass substrates (FTO) followed by conformal electrodeposition of nickel nanoparticles with an average size of 18 nm. Then, in-situ reduction and electrophoretic deposition of graphene oxide (GO) nanosheets on the structured ZnO/Ni electrode was performed. The prepared three-dimensional nanostructure exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 98 publications
0
21
0
Order By: Relevance
“…However, the aspect ratio of the nanowires is larger than that of the nanorods, but the response time of the device based on the nanowire net is not faster than that of our sensor, because the nanowire net contains junctions, which leads to the internal diffusion resistance of chemisorbed oxygen ions. 18 This means that the net carrier density decreases with more junctions in the sensor, leading to a lengthening of the response time. The Nb 2 O 5 nanorod arrays grown with vertical rods on the Nb substrate, moreover, the designed structure of the sensor, resulted in a current along the nanorods, that connected them to the Nb foil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the aspect ratio of the nanowires is larger than that of the nanorods, but the response time of the device based on the nanowire net is not faster than that of our sensor, because the nanowire net contains junctions, which leads to the internal diffusion resistance of chemisorbed oxygen ions. 18 This means that the net carrier density decreases with more junctions in the sensor, leading to a lengthening of the response time. The Nb 2 O 5 nanorod arrays grown with vertical rods on the Nb substrate, moreover, the designed structure of the sensor, resulted in a current along the nanorods, that connected them to the Nb foil.…”
Section: Resultsmentioning
confidence: 99%
“… 10 The RT response time is too long to be useful in practical applications, and may be due to the large amounts of junctions among the nanowires, which slow down the diffusion of gas molecules and increase the electron scattering. 18 Several attempts have been made to decrease the resistance and the response time of network sensors. The methods resulted in either an unavoidable increase in the fabrication cost or the formation of composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the gas sensors made of these 1-D nanostructures offer ultra-sensitivity, fast response, higher stability, low-temperature operations, and less power consumptions 101,102 . Till date, variety of 1-D nanostructures including nanobelts 60,72,73,96,99,[101][102][103][104][105] , nanoribbons 56,59,100,106,107 , nanorods 74,75,97,[108][109][110][111][112][113] , nanofibers 76,114 , nanowires 82 and microrods 98,115,116 of MoO3 have been utilized in gas sensors and the following section summarize about these nanostructures with their gas sensing performance and mechanism. An overview of gas sensors based on 1-D MoO3 nanostructures is listed in Table 1.…”
Section: One Dimensional (1-d) Moo3 Nanostructures For Gas Sensormentioning
confidence: 99%
“…A suitable combination of these 2-D material with oxide nanostructures offers spontaneous electron transfer and ensures that the diffusion of the gas molecule results in improving the sensor response along with optimizing the response/recovery times of the gas sensor 122 . The group of Yang et al 106 demonstrated a one-step HT method for uniformly loading the orthorhombic MoO3 NRbs on the exfoliated graphene oxide (GO) supporting layers (Figure 4f-1). The SEM image in Figure 4f-2 revealed that the as-synthesized products were composed of large amounts of NRbs (length ∼10 μm) loaded on the graphene nanosheets while MoO3 NRbs were also clearly located on either side of the graphene nanosheet in Figure 4f-3.…”
Section: Moo3 Nanoribbons (Nrbs)mentioning
confidence: 99%
“…In addition, as metal oxide exhibits excellent gas sensing properties for H 2 , the graphene-metal oxide hybrid materials are usually used to detect H 2 with low limit of detection (LOD) at room temperature. Wang et al synthesized MoO 3 nanoribbon/graphene hybrid for H 2 sensing with ultralow LOD of 0.5 μL/L (Yang et al, 2017 ). Zhang et al ( 2017c ) reported a high-performance H 2 gas sensor based on CuO/rGO/CuO sandwiched nanostructure.…”
Section: Application Of Gas Sensormentioning
confidence: 99%